Cognitive adaptability and narrow personality traits: Proposing a person–entrepreneurship fit for established entrepreneurs in South Africa - Melodi Botha; Hajo Morallane (South African Journal of Business Management, 2019)
Background: The person–entrepreneurship fit has been confirmed for new ventures, but has not been determined for established entrepreneurs. Personality traits and entrepreneurial cognitions are seen as important factors that lead to long-term performance, which is needed for established entrepreneurs to survive.Objectives: A model is proposed which suggests that a closer association between certain narrow personality traits and the cognitive adaptability dimensions indicates a closer person–entrepreneurship fit.Method: A quantitative approach was followed whereby 2650 established entrepreneurs in South Africa were surveyed, and a multiple regression analysis was conducted.Results: Most studies on personality are conducted using the five-factor model of personality traits, and not necessarily the narrow traits. In this regard, new narrow traits emerged within the five main personality traits. The findings increase the understanding of the cognitive adaptability, and how it relates to these discrete narrow personality traits.Conclusion: The findings of this study may inform the policymakers who are trying to encourage entrepreneurial activity, and the transition of nascent entrepreneurs to established entrepreneurs in the context of developing as well as developed markets. Educators could incorporate the cognitive adaptability dimensions in entrepreneurial training and support programmes, which could encourage nascent and start-up entrepreneurs to become established entrepreneurs.
Keywords: 650